A Manual for Country Economists - Caiola, Marcello (Manuals and Guides, 1995)
This Manual, addressed mainly to new staff members in the area and functional departments of the IMF, presents different ways to tackle specific problems that desk economists encounter in analyzing country data. This guide presents an approach to analyzing financial developments in a country and to evaluating the quality of data at the disposal of the staff.